A poesia plural de Pablo Neruda - Gonzaga, Vera Lígia Mojaes Migliano [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Esta pesquisa de Doutorado tem por objetivo principal evidenciar a pluralidade da poesia de Pablo Neruda (1904-1973), poeta chileno e Prêmio Nobel de Literatura em 1971. Em nossa investigação, realizada à luz da bibliografia especializada na área, utilizamos os pressupostos metodológicos da crítica temática, pretendendo realizar um levantamento estilístico-formal para mostrar a poesia plural do poeta. Sempre trabalhando especificamente com os textos originais (a fim de que não se percam características inerentes ao idioma, tais como a sonoridade, as imagens e os símbolos específicos da língua espanhola) preocupamo-nos também em representar os estilos literários presentes na obra nerudiana. Finalmente, discutimos a pluralidade temática da poesia nerudiana e apontamos a maneira peculiar com a qual o autor usa diversas técnicas de expressão, mesclando, contrapondo, justapondo, modificando e brincando com diversos estilos, diversas formas e diversas vozes em seus poemas

This Doctoral research has as its main goal to show the plurality of Pablo Neruda’s poetry (1904-1973), Chilean poet and Nobel Prize for Literature in 1971. In our investigation, done according to the specialized bibliography on the area, we used the methodological procedures of thematic critics, intending to carry out a formal stylistic survey in order to show the plural poetry of the poet. Always working specifically with the original texts (in order to do not miss important characteristics inherent to the idiom, like the sound, images, specific symbols of the Spanish Language) we also concerned ourselves in representing the literary styles presented in Neruda’s work, Finally, we discuss the thematic plurality of Neruda’s poetry and point out the peculiar way in which the author uses diverse techniques of expression, mixing, opposing, juxtaposing, modifying and playing with diverse styles, forms and voices in his poems
Keywords: Neruda, Pablo, 1904-1973; Literatura chilena; Poesia chilena